Mathematical approaches in artificial intelligence and UAV control problems - Uspenskyi, V. B.; Shyriaieva, Natalia Volodumyrivna (Національний технічний університет "Харківський політехнічний інститут", 2025)
Course Title: Mathematical Approaches in Artificial Intelligence and UAV Control Problems. The course is aimed to familiarize with the general methods of artificial intelligence and the main tasks of UAV control. Course Structure. The course consists of two sections: 1) Methods of artificial intelligence (chapters 1-3) - methods and problems of evolutionary modeling (3 lectures, 1 laboratory work); - fundamentals of fuzzy logic and fuzzy inference systems using the example of control systems (5 lectures, 1 laboratory work); - basic concepts of neural networks and their architecture (4 lectures, 1 laboratory work); 2) UAVs and control tasks (chapter 4) - general information about UAVs, on-board equipment and tasks of its design (1 lecture); - mathematical model of controlled multicopter movement, general algorithms and flight control algorithms (2 lectures, 3 laboratory works); - perspective tasks in UAV group management and solving methods (1 lecture). The description of laboratory work is attached as an Appendix.
Keywords: artificial intelligence; mathematical approaches; UAV control; genetic algorithm; fuzzy sets theory; fuzzy inferencesystem